Mobile Information Systems: An Empirical Analysis of the Determinants of Mobile Commerce Acceptance in Jordan - Al-Najjar, Ghassan M. (2012)
Although mobile commerce have been used and widely researched in developed nations, there is a low usage in the Arab world. Also, there is a limited empirical research on mobile commerce in Jordan despite the high penetration of mobile phone subscribers in 2009. Among the aims of this quantitative research is to empirically investigate the determinants of mobile commerce adoption in a collectivist culture such as Jordan where social norms are valued and individual actions are influenced greatly by important reference groups. The Technology Acceptance Model (TAM) is extended to include four factors (facilitating conditions, cost, personal innovativeness in IT (PIIT) and subjective norms). Furthermore, in order to understand subjective norms in collectivist culture; subjective norms were decomposed into different levels (personal and societal injunctive and descriptive norms). The research framework consists of twelve latent variables (seven exogenous and five endogenous). Using self-administered survey, 40 items with 7-point Likert scale is used to collect data. Out of the 500 samples, 448 responses (89.6 % response rate) were collected; eventually 401 responses were usable. Structural Equation Modeling is applied to analyze the data. The findings of this study revealed that facilitating conditions, cost, PIIT, attitude and perceived usefulness are significant determinants of behavioral intention in Jordan. In addition, subjective norms, facilitating conditions, cost and perceived ease of use are significant antecedents of attitude which in turn influencing behavioral intention. Moreover, the empirical evidence indicated that personal injunctive norm, personal descriptive norm and societal injunctive norm are indeed antecedents of subjective norms. It can be concluded that extended TAM successfully enriched the model and increased the exploratory power to 53% in explaining behavioral intention variance.